2009
DOI: 10.28945/127
|View full text |Cite
|
Sign up to set email alerts
|

Design Alternatives for a MediaWiki to Support Collaborative Writing

Abstract: Web 2.0 technologies are having a considerable influence on the learning industry. Constructivist learning processes, such as collaborative writing, have emerged as a result of the development of Web 2.0 technologies. We define the term "mandatory collaborative writing" to describe a writing task where the group has a firm deadline. This article focuses on how a wiki can fully support mandatory group writing. The motivation of this design science research study emerges from a graduate Knowledge Management clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Heafner and Friedman (2009) suggest that wikis used in secondary social studies facilitated a pedagogical shift from traditional teacher-centered instruction to student-oriented and constructivist learning. Likewise, Kasemvilas and Olfman (2009) pointed out that that MediaWiki could better facilitate the collaborative writing process with some extensions that support discussion and project management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Heafner and Friedman (2009) suggest that wikis used in secondary social studies facilitated a pedagogical shift from traditional teacher-centered instruction to student-oriented and constructivist learning. Likewise, Kasemvilas and Olfman (2009) pointed out that that MediaWiki could better facilitate the collaborative writing process with some extensions that support discussion and project management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…setting a deadline or defining different goals of an individual's writing task, and led to a set of extensions and design principles to facilitate group writing and constructivist learning processes (Kasemvilas and Olfman, 2009). Research on the implementation of cognitive group awareness tools to support controversial discussions has been conducted on online forums showed that making contributions more salient could strengthen a group's influence on others and foster learning processes (Buder and Bodemer, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In higher education settings, research has been carried out on a wide range of subjects related to wikis, including issues as didactic and organizational arrangements for learning, design of open learning environments, and knowledge production (Baltzersen, 2010;Bonk, Lee, Kim, & Ling, 2009;Hadjerrouit, 2013;Karasavvidis, 2010;Kasemvilas & Olfman, 2009;Pusey & Meiselwits, 2009;Rice, 2009;Su & Beaumont, 2010;Trentin, 2009). (Brodahl et al, 2011, p. 74) However the use of Google Docs (2008) and EtherPad (2008), being collaborative writing tools relatively comparable to wikis, remains a gap in research literature (Benson, 2012;Chu & Kennedy, 2011), though recently a number of contributions to the body of research have been made (Brodahl et al, 2011;Burden, 2012;Caspi & Blau, 2011;Cruz, Dominguez, Maia, Pedrosa, & Grams, 2013;Dishaw, Eierman, Iversen, & Philip, 2013;Garner, 2010;Oguilve, Vindas, & Moya, 2012;Tomlinson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%